Trophic ecology of the facultative symbiotic coral Oculina arbuscula - Leal, Miguel C. (2014)
Symbiotic corals are trophically complex, relying on both auto- and heterotrophy. Here, the nutrition of the temperate facultative symbiotic scleractinian coral Oculina arbuscula was investigated under natural conditions. Nutrition of symbiotic and aposymbiotic colonies during spring and fall was assessed by determining the carbon and nitrogen isotope signature of their tissues, photosynthetic endosymbionts and different potential food sources (plankton and particulate organic matter) in seawater and sediment. The nutrition of symbiotic colonies was primarily derived from their endosymbionts, regardless of the season. However, aposymbiotic colonies of O. arbuscula relied preferentially on sediment organic matter as well as pico- and nanoplankton (<10 µm). As this small planktonic fraction (that includes phytoplankton) has been overlooked as a potential food source for symbiotic scleractinian corals, this study provides new insights into this feeding mode in these reef-building organisms.